2016
DOI: 10.1186/s12888-016-0939-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence rates of borderline personality disorder symptoms: a study based on the Netherlands Mental Health Survey and Incidence Study-2

Abstract: BackgroundDespite increasing knowledge of the prevalence of borderline personality disorder (BPD) in the general population, and rising awareness of mental disorders both as a categorical and a dimensional construct, research is still lacking on the prevalence of the number of BPD symptoms and their associated consequences, such as comorbidity, disability, and the use of mental health services) in the general population.MethodsData were obtained from the second wave of the Netherlands Mental Health Survey and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 33 publications
4
83
0
4
Order By: Relevance
“…With respect to PDs, borderline PD was, as expected, the greatest risk for suicide attempt, the number of BPD symptoms was associated with more frequent suicidal behavior. 28 In contrast, a report from China revealed that "cluster B" PDs, including borderline PD, were not significantly associated with attempted suicide;…”
Section: Discussionmentioning
confidence: 95%
“…With respect to PDs, borderline PD was, as expected, the greatest risk for suicide attempt, the number of BPD symptoms was associated with more frequent suicidal behavior. 28 In contrast, a report from China revealed that "cluster B" PDs, including borderline PD, were not significantly associated with attempted suicide;…”
Section: Discussionmentioning
confidence: 95%
“…These children were interviewed with the UK Childhood Interview for DSM-IV Borderline Personality Disorder (UK-CI-BPD), which was based on the Diagnostic Interview for DSM-IV Personality Disorders (DIPD-IV) but has modified language, content, and structure to accommodate juvenile respondents. 6,330 children gave complete interviews.Finally, ten Have and colleagues26 reported on BPD prevalence among adults in the Netherlands, using a sample from the Netherlands Mental Health Survey and Incidence Study-2…”
mentioning
confidence: 99%
“…Wenn Eifersucht und Wut ihn "übermannen" würden, könne er nichts dagegen tun, würde "ausrasten". [6,7].…”
Section: Symptomatik Der Borderline-persönlichkeitsstörungunclassified